Anthelmintic Potential of Unriped Banana Kepok (Musa paradisiaca L.) Extract Against Ascaris suum In Vitro - Muhammad Ubaid Khoir (Journal of Basic Medical Veterinary, 2023)
The aim of this study was to determine concentration, soaking time, interaction between concentration and soaking time of methanol extract of kepok banana unriped fruit to cause death toward Ascaris suum in vitro. Research design that has been used in the research was completely randomized design. This research used 300 samples of Ascaris suum with length 10-20 cm without differentiating their sex. Concentration of methanol extract of kepok banana unriped fruit were 10%, 20% and 40%. Physiological NaCl, CMC-Na and Piperazine citrate 10 mg/ml were being used as control. Each treatment then being replicated five times. The observation and recording of dead worm were done at 2, 4, 6, 8 and 10 hours. Ascaris suum were declared dead if there was no movement while disturbed by anatomy tweezers and dipped in slightly warm water (50 ºC). The obtained data was analyzed using ANOVA Factorial and continued with Duncan Multiple Range Test by SPSS 26 for Windows. The result was 40% concentration and exposure time for 10 hours caused the most mortality toward Ascaris suum. Interaction between concentration and exposure time resulted 40% concentration methanol extract of unriped kepok banana fruit in 10 hours caused the most mortality towards Ascaris suum.